2022
DOI: 10.1021/acsami.2c17889
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Separation of Aromatic Amine Isomers: A Solved Issue by a New Amphiphilic Pillar[6]arene Stationary Phase

Abstract: In this work, the fabrication, synthesis, and characterization of a new stationary phase based on an amphiphilic pillar[6]arene (P6A-C10-2NH2) for gas chromatographic analyses are reported. The gas chromatography (GC) column prepared with P6A-C10-2NH2 stationary phase exhibited a medium polarity, an efficiency of 3219 plates/m, and unmatched resolving capabilities toward chloroaniline, bromoaniline, iodoaniline, and toluidine isomers. Furthermore, the P6A-C10-2NH2 column showed excellent repeatability with max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Table 1 presents the measured McReynolds constants of PCL-GIL, PCL-2OH and HP-35 columns with five solutes involving benzene, 1-butanol, 2-pentanone, 1-nitropropane, pyridine, where each value showed the retention strength of stationary phase for the solute molecules. [39,40] As shown, the average value (174) of PCL-GIL stationary phase reflected moderate polarity, between the values of PCL-2OH and commercial HP-35 columns. This result indicates the possible difference in chromatographic selectivity.…”
Section: Characterization Of Pcl-gil and Pcl-2oh Stationary Phasementioning
confidence: 85%
“…Table 1 presents the measured McReynolds constants of PCL-GIL, PCL-2OH and HP-35 columns with five solutes involving benzene, 1-butanol, 2-pentanone, 1-nitropropane, pyridine, where each value showed the retention strength of stationary phase for the solute molecules. [39,40] As shown, the average value (174) of PCL-GIL stationary phase reflected moderate polarity, between the values of PCL-2OH and commercial HP-35 columns. This result indicates the possible difference in chromatographic selectivity.…”
Section: Characterization Of Pcl-gil and Pcl-2oh Stationary Phasementioning
confidence: 85%
“…96 To date, PA[ n ]-based NACs have been used to separate cis – trans isomers. 97 For example, Huang and co-workers found that H2 β was an efficient material for the separation of cis – trans isomers of 1,4-dichloro-2-butene ( DCB ) (Fig. 3-I).…”
Section: Pillar[n]arene-based Nacsmentioning
confidence: 99%
“…However, P[n]As has few applications in GC separations. Besides the preceding works of our group, [32][33][34] only Qi et al reported a permethyl pillar [5]arene (MP5) capillary column prepared by the sol-gel coating method. And the MP5 column presented a particular retention of dibromoalkanes and high resolution of various isomers.…”
Section: Introductionmentioning
confidence: 99%